Phylogenetic position of a bizarre lizard Harpesaurus implies the co-evolution between arboreality, locomotion, and reproductive mode in Draconinae (Squamata: Agamidae). Issue 7 (8th August 2020) - Kurita, Takaki; Kojima, Yosuke; Hossman, Mohamad Yazid; Nishikawa, Kanto
Abstract : Viviparous reproduction has evolved independently more than 100 times in the evolutionary history of Squamata (lizards and snakes). Adaptation to cold climates is the dominant hypothesis explaining shifts to viviparity, but viviparous species are also present in the tropical lowlands, implying the presence of other factors that may also promote the evolution of viviparity. For example, the tropical Asian/Oceanian subfamily, Draconinae, includes two viviparous genera ( Cophotis and Harpesaurus ). However, one of them, Harpesaurus, is extremely rare, making it difficult to study aspects of their ecology or evolution. We managed to collect a H . borneensis, and this provided an opportunity to address the evolution of viviparity in draconine lizards. Based on a new molecular phylogenetic hypothesis, including all viviparous groups in Draconinae, we infer that viviparity has evolved twice within the subfamily. Ancestral state reconstruction analyses indicated that shifts to viviparity were preceded by the evolution of arboreality and slow-moving locomotion. Our analysis strongly suggests evolutionary correlations between habitats, locomotion, and reproductive modes. Taken together, these results suggest that the use of arboreal habitats and slow locomotion facilitated the evolution of viviparity in these tropical/subtropical lizards. Arboreal, slow-moving species are considered to rely more on crypsis in predator avoidance rather than fleeing. Therefore, we propose that such species are relatively insusceptible to the concomitant cost of viviparity: reduced locomotive ability and increased risk of predation during pregnancy. We also describe and discuss the unique behaviours of H . borneensis .